Book review: Rodriguez, CO. 2018. Decolonizing academia - poverty, oppression and pain. Nova Scotia: Fernwood. - Naiefa Rashied (University of Johannesburg, 2019)
Naeifa Rashied argues that Clelia Rodriguez' book Decolonizing academia - poverty, oppression and pain "does a lot more than reflect on curriculum. Its unconventional, poetic, first-person tone highlights injustices experienced from all angles in higher education which makes it a valuable read". How to cite this book review: RASHIED, Naiefa. Book review: Rodriguez, CO. 2018. Decolonizing academia - poverty, oppression and pain. Nova Scotia: Fernwood. Scholarship of Teaching and Learning in the South. v. 3, n. 1, p. 113-114, Apr. 2019. Available at: https://sotl-south-journal.net/?journal=sotls&page=article&op=view&path%5B%5D=104&path%5B%5D=38 This work is licensed under the Creative Commons Attribution 4.0 International License. To view a copy of this license, visit http://creativecommons.org/licenses/by/4.0/